Dynamics of left-right party positions : separating systematic movements from noise - McDonald, Michael D. (2002)
We investigate whether it is feasible to use the Comparative Manifesto Project (CMP) data on party positioning to take account of party movements along the left-right dimension. At issue are answers to two questions. Are there discernable dynamics in party positions? And, if so, is it possible to separate systematic party dynamics from measurement error so as to make effective use of the CMP data? The answer to both questions is yes. Our analysis of 81 parties across the post-War period detects systematic movements in the left-right positions for one third of the parties. Our analysis of measurement error reveals that, as measured by the CMP, about 65% of the variance in party positions records reliable long-term differences across parties, another 16% records systematic movements, and the remaining 19% is error. We conclude with discussions of what one should make of this mix of stability, movements, and error and what one should do about it when using the CMP data to analyze substantively important questions about politics and policy. Of particular importance are our recommendation to be ever mindful of the two possible sources of error—a faulty instrument and erratic behavior on the part of parties themselves—and our suggestion for how to separate or combine those possibilities depending on one’s theoretical concern.